Pelatihan Digital Marketing Sebagai Upaya Peningkatan Perekonomian Pada Sektor UMKM Kelurahan Blitar - Oggi defa Adetya; Laksmi Diana, S.S, M.Pd; Maharani Ikaningtyas S.E., M.AB; Ferdiana Nur Puspakaritas (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
In the business world, digital marketing is often used in marketing. This is supported by rapid technologicaldevelopments and an increase in the number of internet users, but it turns out that many UMKM have notimplemented it, such as in the Blitar Village. The problem faced by UMKMs in the Blitar Village is that marketingis still conventional due to a lack of knowledge related to digital marketing and technology. Knowing this, group 16held a digital marketing training program for UMKMs in the Blitar Village. The purpose of this program is toprovide education about digital marketing, and assistance in creating online media accounts. The methods usedinclude observation, preparation, implementation, and evaluation. The results of this program are D'Celvin and“Cap Ceret'' Coffee's social media accounts. It is hoped that the results of this program can help UMKMs to expandtheir market and develop their business.